Autonomic nervous system function predicts the inflammatory response over three years in newly diagnosed ulcerative colitis patients. Issue 11 (6th June 2016) - Gunterberg, V.; Simrén, M.; Öhman, L.; Friberg, P.; Jones, M. P.; Van Oudenhove, L.; Strid, H.
Abstract: Background: The autonomic nervous system (ANS) modulates intestinal inflammation in animal models. Human evidence confirming such modulating influence is limited. We aimed to investigate whether ANS function is associated with inflammatory parameters at disease onset, and whether it predicts the evolution of inflammation in patients with ulcerative colitis (UC). Methods: We prospectively monitored 51 patients from onset of UC for 3 years. Upon remission of the onset flare, ANS activity was assessed by heart rate variability analysis and compared with healthy controls. Inflammatory parameters in blood, stool, and colonic biopsies obtained at onset and during follow‐up visits were analyzed. Generalized linear models were used to test cross‐sectional associations between ANS activity and inflammatory parameters at onset; linear mixed models were used to test whether ANS function at onset predicted the evolution of inflammation over the following 3 years. Key Results: Sympathovagal balance was different in UC patients compared to healthy controls, and cross‐sectional associated with higher levels of systemic (erythrocyte sedimentation rate [ESR], CRP, TNF‐ α, IFN‐ γ ) and mucosal inflammation (interleukin‐8, IFN‐ γ ) at onset. Conversely, a negative cross‐sectional association with parasympathetic activity was found for ESR & TNF‐ α . Longitudinally, parasympathetic activity at onset predicted systemic (ESR, WBC), but not mucosal inflammation during follow‐up. Conclusions & Inferences: This study further strengthens the association between the ANS system and intestinal inflammation previously found in animal models and recently in patients with inflammatory bowel disease. These results may have important implications for the pathogenesis and treatment of UC. Abstract : This study confirms the close interplay between ANS and the immune system in patients with UC as previously shown in animal models of intestinal inflammation and recently in patients with IBD. We demonstrated both a cross‐sectional association between autonomic activity and inflammation upon remission of the onset flare, and also a prediction of the inflammatory activity over a 3‐year follow‐up period.